2018
DOI: 10.3389/fpsyg.2018.00698
|View full text |Cite
|
Sign up to set email alerts
|

Early Reputation Management: Three-Year-Old Children Are More Generous Following Exposure to Eyes

Abstract: To enhance their reputations, adults and even 5-year-old children behave more prosocially when being observed by others. However, it remains unknown whether children younger than five also manage their reputations. One established paradigm for assessing reputation management is the ‘watching eyes paradigm,’ in which adults have been found to be more prosocial in the presence of eyes versus control images. However, the robustness of this effect in adults has recently been called into question, and it has never … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Alongside these issues, our findings raise important theoretical questions related to why pre-schoolers resource allocation rates differed with high-and low-merit co-workers. Before considering the richer merit-based account, it is important to note here that our data could also be interpreted as providing support for either a lean associationist or a reputational management account [40,41,42]. Regarding the former, it may be argued that pre-schoolers within this study simply formed a more positive association with the puppet that was linked to the conferring of the stickers.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Alongside these issues, our findings raise important theoretical questions related to why pre-schoolers resource allocation rates differed with high-and low-merit co-workers. Before considering the richer merit-based account, it is important to note here that our data could also be interpreted as providing support for either a lean associationist or a reputational management account [40,41,42]. Regarding the former, it may be argued that pre-schoolers within this study simply formed a more positive association with the puppet that was linked to the conferring of the stickers.…”
Section: Discussionmentioning
confidence: 70%
“…Due to the co-worker puppet remaining present during the sharing task, it could also be argued that any tendency to share more with a high merit puppet may to some degree also be due to pre-schoolers desire to manage their reputation [42]. Such reasoning (e.g., thinking about what the puppet would think about them) involves more advanced forms of social understanding (e.g., second order false belief), and is considered to be beyond the capabilities of pre-schoolers [47].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have found no evidence for the watching-eye effect in children 90,91 . However, a third study, which used real photos of eyes rather than stylized images and primed children with the test stimuli prior to the experiment, did find evidence of the watching-eye effect in pre-schoolers 92 . The authors posited that without the priming, the infants did not attend to the eyes during the experiment.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, children become increasingly aware between these ages that they are being seen and evaluated by others and that their behaviors convey important social information to others (Engelmann & Rapp, 2018; Vaish & Tomasello, 2014). For instance, 3-year-olds engage in some self-presentation behaviors such as lying after cheating (Evans & Lee, 2013) and increasing their prosocial behavior under cues of being observed (Kelsey, Grossmann, & Vaish, 2018), perhaps to present themselves in a positive light. Children of this age may thus begin to recognize the importance of showing one’s commitment to others, such as by repairing harm that one caused or reciprocating help one received.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%